EFEKTIVITAS LAYANAN BIMBINGAN KELOMPOK DALAM MENINGKATKAN KOMUNIKASI ASERTIF - Meilany Muskita, Sherly (Widya Warta, 2017)
The research purpose was to analyze the effectiveness of group counseling services in enhancing assertive communication behaviors. Subjects were students of Guidance and Counseling study program of Widya Mandala Catholic University of Madiun in 2014/2015 Academic Year. The testing of the effectiveness of group counseling services in improving assertive communication behaviors used one group pre test post test method. The results of calculation of numerical t = 14 468 with 7 degrees of freedom at odd errors 0.003 (significant). The rule used was to test the alternative hypothesis (Ha) saying that group counseling services could significantly improve the behaviors of assertive communication. It can be concluded that the group counseling services are effective to improve the behaviors of assertive communication